PENENTUAN NILAI EKSAK DARI HARGA OPSI TIPE EROPA DENGAN MENGGUNAKAN MODEL BLACK-SCHOLES - Irwan Irwan (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
This writing aims to analyze model black-scholes in the determination of the value of inexact from the price of an option type europe as well as simulasinya. The data used is information call option and put option for closing as well as the closing price ( price ) shares barnes group inc. The first thing is done by searching volatility stock prices to call option and put option. Based on the result analysis inexact terhadap the ordinal value from the price of call option and put option to use the model of black-scholes obtained the price of fair to call option is as much as 3.4940, on the circumstances of this the seller and buyer call option for achieving the break-even point. To put or libya option is as much as 0.0329, on the circumstances of it ' s called out of the money where a put option zero-sum and will not be executed. Next simulation model black-scholes in the determination of the value of inexact from the price call option and put option. The results of the simulation concluded that the longer time left to maturity hence the higher the price of an option.